Normative Study of the Binaural Interaction Component of the Human Auditory Brainstem Response as a Function of Interaural Time Differences. Issue 3 (May 2021) - Sammeth, Carol A.; Greene, Nathaniel T.; Brown, Andrew D.; Tollin, Daniel J
Abstract : Objectives: The binaural interaction component (BIC) of the auditory brainstem response (ABR) is obtained by subtracting the sum of the monaural right and left ear ABRs from the binaurally evoked ABR. The result is a small but prominent negative peak (herein called "DN1"), indicating a smaller binaural than summed ABR, which occurs around the latency of wave V or its roll-off slope. The BIC has been proposed to have diagnostic value as a biomarker of binaural processing abilities; however, there have been conflicting reports regarding the reliability of BIC measures in human subjects. The objectives of the current study were to: (1) examine prevalence of BIC across a large group of normal-hearing young adults; (2) determine effects of interaural time differences (ITDs) on BIC; and (3) examine any relationship between BIC and behavioral ITD discrimination acuity. Design: Subjects were 40 normal-hearing adults (20 males and 20 females), aged 21 to 48 years, with no history of otologic or neurologic disorders. Midline ABRs were recorded from electrodes at high forehead (Fz) referenced to the nape of the neck (near the seventh cervical vertebra), with Fpz (low forehead) as the ground. ABRs were also recorded with a conventional earlobe reference for comparison to midline results. Stimuli were 90 dB peSPL biphasic clicks. For BIC measurements, stimuli were presented in a block as interleaved right monaural, left monaural, and binaural stimuli with 2000+ presentations per condition. Four measurements were averaged for a total of 8000+ stimuli per analyzed waveform. BIC was measured for ITD = 0 (simultaneous bilateral) and for ITDs of ±500 and ±750 µs. Subjects separately performed a lateralization task, using the same stimuli, to determine ITD discrimination thresholds. Results: An identifiable BIC DN1 was obtained in 39 of 40 subjects at ITD = 0 µs in at least one of two measurement sessions, but was seen in lesser numbers of subjects in a single session or as ITD increased. BIC was most often seen when a subject was relaxed or sleeping, and less often when they fidgeted or reported neck tension, suggesting myogenic activity as a possible factor in disrupting BIC measurements. Mean BIC latencies systematically increased with increasing ITD, and mean BIC amplitudes tended to decrease. However, across subjects, there was no significant relationship between the amplitude or latency of the BIC and behavioral ITD thresholds. Conclusions: Consistent with previous studies, measurement of the BIC was time consuming and a BIC was sometimes difficult to obtain in awake normal-hearing subjects. The BIC will thus continue to be of limited clinical utility unless stimulus parameters and measurement techniques can be identified that produce a more robust response. Nonetheless, modulation of BIC characteristics by ITD supports the concept that the ABR BIC indexes aspects of binaural brainstem processing and thus may prove useful in selected research applications, e.g. in the examination of populations expected to have aberrant binaural signal processing ability.